Hidden Hoards in the Holy Land in the Records of Nineteenth-Century Western Travelers - Arbel, Yoav (Antiguo Oriente, 2026)
The nineteenth century brought an influx of pilgrims, explorers and adventurers into the Holy Land. Most travelers kept to the traditional pilgrimage routes, yet others ventured into regions few Europeans dared to visit, facing rough conditions, hostile populations in some places and the dangers of the road. Many of them published their records in textual, cartographic, artistic and eventually photographic volumes that reached large audiences that were otherwise familiar with the land only from the biblical and historical texts of antiquity. Other than the sacred sites, many Western authors referred to the cultural and social aspects of the communities they met. One of the phenomena they found most intriguing, perplexing as well as disturbing was the obsession with hoards and treasures secretly stashed away for protection in calm or turbulent times. The numerous related references in travelers’ records to both ancient and recent hoards reflect the perspectives of Europeans and Americans of the era on that peculiar subject, and through it on the broader scene of traditions, customs, thoughts, attitudes and life modes in one of the most complex provinces of the Ottoman empire.